Research highlights: microfluidic analysis of antimicrobial susceptibility. Issue 5 (28th January 2015) - Murray, Coleman; Adeyiga, Oladunni; Owsley, Keegan; Di Carlo, Dino
Abstract : Single-cell morphological analysis – gradient antibiotic susceptibility – rapid bacterial detection in blood. Abstract : Antimicrobials remain an integral part of the treatment of patients with an infection. New microfluidic technologies are poised to help clinicians prescribe the right antimicrobials, sooner, reducing long hospital stays and improving outcomes. Given that current microbiologic diagnostic testing methods require a significant turnaround time (days), clinicians, in general, initially empirically determine a suitable therapy. After review of laboratory data, including information regarding the susceptibility of the microbial pathogen to specific anti-infectives, a clinician will then make alterations in therapy as appropriate, to direct therapy toward the pathogen involved in the illness. Important steps needed to quickly ascertain this information include the timely isolation of the microorganism, followed by direct antibiotic susceptibility tests (ASTs) or determination of the presence within the microorganism of any resistance genes or proteins that will impair the activity of a potential therapy. Recent microfluidic technologies highlighted here that can intrinsically interface at the scale of the organisms are starting to address these challenges by improving the speed and accuracy of tests aimed at helping physicians to give the right antimicrobials sooner.